Quality of referral system and associated factors among referred clients referred to dessie comprehensive specialized hospital, Northeast, Ethiopia - Biruk Abera; Toyib Yasin; Hiwot Gizaw; Yonas Fissha Adem (PLoS ONE, 2025)
Background An effective referral system acts as a connection among the three tiers of healthcare in Ethiopia, ensuring the seamless provision of appropriate health services. The success of the referral system is a key factor influencing the overall quality and strength of healthcare delivery. Therefore, this study aimed to assess the quality of the referral system and associated factors among referred clients at Dessie Comprehensive Specialized Hospital, Northeast Ethiopia. Methods A facility-based cross-sectional study was conducted on 413 referred patients at Dessie Comprehensive Specialized Hospital from January 15, 2023, to February 15, 2023. The study participants were selected using a systematic random sampling technique. Data entry and processing were performed using EpiData version 4.4.2 and exported to SPSS version 26.0 for further analysis. Both bivariate and multivariable binary logistic regression analyses were used to identify factors associated with the quality of the referral system. Crude odds ratios (COR) and adjusted odds ratios (AOR), along with 95% confidence intervals (CI), were calculated. A p-value < 0.05 in the final model was considered statistically significant. This study assessed the referral system’s structure (forms, transport registers, focal persons), process (14 referral paper components like patient details and reasons), and outcomes (patient satisfaction surveys). Result The overall quality of the referral system to Dessie Comprehensive Specialized Hospital was 62.5% (95% CI: 57.6%–66.8%). The overall input quality of the referral system was 90.3% (95% CI: 87.7%–93.2%), and the overall process quality was 88.3% (95% CI: 86.5%–91.6%). Patient satisfaction was 44.6% (95% CI: 40.0%–49.2%). Transport mode was significantly associated with the quality of the referral system: patients transported by ambulance [AOR: 6.59, 95% CI: 3.49–12.43], by vehicle [AOR: 5.62, 95% CI: 2.33–10.52], by public taxi [AOR: 3.82, 95% CI: 1.25–8.65], and those referred from rural areas [AOR: 0.33, 95% CI: 0.19–0.56]. Conclusion Generally, a significant proportion of referred clients received poor referral quality. Improvements are needed by establishing and facilitating a transportation mechanism and a feedback system.